Artificial Intelligence Impact on the Sustainable Entrepreneurial Process - Ahmić, Azra; Šahović, Lejla Ahmić (Journal of Ecohumanism, 2025)
In the face of pressing socio-economic and environmental challenges, such as climate change, resource depletion, and social inequality, entrepreneurs are increasingly compelled to embrace innovative strategies that harmonize profitability with social and environmental stewardship. Artificial Intelligence (AI) holds promise in facilitating such solutions but requires careful examination to ensure its effective and ethical deployment in pursuit of sustainability objectives. The primary goal of this study was to ascertain whether AI significantly influences the sustainable entrepreneurial process. This comprehensive research framework integrates concepts from entrepreneurship, stakeholder theory, and digital technology, offering a multifaceted perspective. We employed the multiple regression analysis to examine data gathered from 40 entrepreneurs operating within the Bosnia and Herzegovina settings. The study's outcomes revealed that AI positively and significantly impacts the sustainable entrepreneurial process and its five sub-dimensions: “idea generation, opportunity recognition, opportunity development, venture launch, and positive impact”. This study enriches the literature on AI and sustainable entrepreneurship by offering empirical support for the impact of AI on the sustainable entrepreneurial process while also introducing and validating measurement tools for the sustainable entrepreneurial process. Additionally, entrepreneurs can utilize the findings of this research to strategically incorporate AI into their business processes and product/service innovation, improve operational efficiency, reduce costs, mitigate risks, enhance decision-making, foster collaboration across stakeholders, and capitalize on opportunities effectively.